Efek Radiasi Sinar Gamma pada Pertumbuhan Vegetatif Anggrek Vanda Hibrid - Hartati, Sri; Setiawan, Abednego Widya; Sulistyo, Trijono Djoko (Agrotechnology Research Journal, 2022)
Orchids are one of the most important ornamental plants in the world. The existence of natural orchids in their habitat is approaching extinction rate, so it is necessary to increase the diversity of orchids by crossing them. The Vanda orchid is one of the famous orchids in Indonesia because of its uniqueness. Vanda orchids have a very abundant diversity, so they can increase the potential of orchid plants. This study used a hybrid orchid plant Vanda celebica x Vanda dearei irradiated by Gamma-rays with a dose of 0 Gray, 10 Gray, 20 Gray, 30 Gray, 40 Gray, and 50 Gray. The data obtained from the observations will be analyzed using descriptive methods by observing each plant in various doses of Gamma-ray radiation compared with control treatment and presented in the form of boxplot images. The irradiation dose of hybrid Vanda orchids (Vanda celebica x Vanda dearei) increased the diversity in the parameters of plant height and leaf width. The application of a dose of Gamma-ray irradiation did not cause a significant interaction with the variable number of leaves. The diversity value decreased in the parameters of leaf length and number of roots. Application doses of Gamma-ray irradiation of 10, 20, and 30 Gray can change the leaves into grooves compared to control plants. Mutant plants had lower chlorophyll content than control plants (0 Gray).